Peningkatan overall equipment effectiveness (OEE) mesin grinding pada produksi cokelat bubuk di PT ABC - Bambang Herry Purnomo; Noer Novijanto; Fikria Silfa Maeline (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Maintenance of production machines is the key to success for increasing the efficiency of production machines. The value of OEE (overall Equipment Effectiveness) is an important indicator of the level of effectiveness of production machines. The grinding machine at the cocoa powder company PT ABC Sidoarjo is a production machine that is considered to have the greatest contribution to achieving OEE values. However, up to now, the machine maintenance is only corrective so it has the potential to harm the company. The purpose of this study is to determine the effectiveness of the grinding machine and formulate recommendations for improvement. The method used is the six big losses analysis technique to identify the dominant type of loss, and the FTA (Fault Tree Analysis) technique to determine the root cause. The results of the analysis show that the OEE value of the grinding machine is only 45% (low). The types of losses that contributed greatly to these conditions were reduced speed losses by 41% and were categorized as bad. This is due to the absence of regular replacement of the grinding machine blades so that their performance is less stable. In addition, the values of idling and minor stoppages and set up and adjustment losses are also categorized as bad because of the frequent occurrence of wasted processing time. Only rework losses are categorized as good. A low OEE value indicates that the machine is still not working effectively. Recommendations for improvements that can be done are performing independent maintenance, forming a competent small group, arranging planned maintenance for replacing machine blades and installing vibrators on peripheral pipes